Cervical cancer screening utilization among women aged 30-49 years in Lampung, Indonesia - Johan Hadi Saputra; Lolita Sary; Nova Muhani (Malahayati International Journal of Nursing and Health Science, 2023)
Background: Cervical cancer ranks second with a total of 36,633 cases or 9.2% of the total cancer cases in Indonesia. Cervical cancer patients in Indonesia have reached 23.4 per 100,000 population with an average death rate of 13.9 per 100,000 population.Purpose: To determine the relationship between perceptions of benefits, threats, and barriers to the interest in undergoing cervical cancer screening using the VIA method in women aged 30-49 years in Gedung Rejo Sakti Tulang Bawang Health Center in 2023.Method: Using a quantitative analytical method with a cross-sectional design. The total sample size was 70 people. The sampling method used was accidental sampling. Data analysis was performed using the chi-square test and multivariate analysis using multiple logistic regression.Results: There is a significant relationship between the perception of benefits and the interest in undergoing cervical cancer screening using the VIA method (P-value = 0.000; OR = 0.099), there is a significant relationship between the perception of threats and the interest in undergoing cervical cancer screening using the VIA method (P-value = 0.000; OR = 0.012), there is a significant relationship between the perception of barriers and the interest in undergoing cervical cancer screening using the VIA method (P-value = 0.000; OR = 0.108), the perception of threats is the dominant factor in determining the interest in undergoing cervical cancer screening using the VIA method (P-value = 0.000; OR = 95.782).Conclusion: All variables (perception of benefits, perception of threats, perception of barriers) are closely related to the interest in undergoing cervical cancer screening using the VIA method.Suggestion: Health center management should be more active in health promotion to increase the interest in undergoing cervical cancer screening using the VIA method in women aged 30-49 years.